2019
DOI: 10.1049/iet-nbt.2018.5417
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient polyethylene glycol‐functionalised gold nanorods for photothermal ablation of hepatocellular carcinoma cells

Abstract: Gold nanorods (GNRs) with exceptional photothermal properties have held promising potential for application in the biomedical field. In this study, the authors achieved photothermal ablation by polyethylene glycol (PEG)-functionalised GNRs. Well-dispersed and uniform GNRs were produced through a seed-mediated growth method. A thermal camera was used to scrutinise the temperature distribution and efficiency of the photothermal properties of the GNRs, which were irradiated by an 808 nm laser on a silicon chip. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…PEG can remove approximately 88.9% of the CTAB bound to AuNRs surfaces, thereby improving biocompatibility and structural stability, preventing material morphology and thermal resistance changes, and changing AuNRs surface pharmacokinetics without affecting their photothermal ablation ability (Fig. 3 A) [ 54 , 55 ]. Polydopamine (PDA) promoted the functionalization of biomolecules on the surface of AuNRs, which could enhance the physiological stability and biocompatibility of the nanostructures, further allowing the AuNRs to achieve cell targeting and photothermal killing of cancer cells [ 56 ].…”
Section: Functionalized Aunrs Photothermal Agentsmentioning
confidence: 99%
“…PEG can remove approximately 88.9% of the CTAB bound to AuNRs surfaces, thereby improving biocompatibility and structural stability, preventing material morphology and thermal resistance changes, and changing AuNRs surface pharmacokinetics without affecting their photothermal ablation ability (Fig. 3 A) [ 54 , 55 ]. Polydopamine (PDA) promoted the functionalization of biomolecules on the surface of AuNRs, which could enhance the physiological stability and biocompatibility of the nanostructures, further allowing the AuNRs to achieve cell targeting and photothermal killing of cancer cells [ 56 ].…”
Section: Functionalized Aunrs Photothermal Agentsmentioning
confidence: 99%
“…28 In addition, Du et al reported the highly efficient poly(ethylene glycol)-capped GNRs for photothermal ablation (PTA) of hepatocellular carcinoma. 29 Also, a plethora of reports is available on the surface modification of GNRs for improved drug delivery applications. 30−32 This article is licensed under CC-BY-NC-ND 4 In oncology, GNPs are prominent agents that aid in the conversion of radiations into heat.…”
Section: Introductionmentioning
confidence: 99%
“…Mirza and Shamshad fabricated doxorubicin-functionalized PSS-coated GNRs to resist CTAB . In addition, Du et al reported the highly efficient poly­(ethylene glycol)-capped GNRs for photothermal ablation (PTA) of hepatocellular carcinoma . Also, a plethora of reports is available on the surface modification of GNRs for improved drug delivery applications. …”
Section: Introductionmentioning
confidence: 99%